The complete chloroplast genome sequence of Brachypodium distachyon: sequence comparison and phylogenetic analysis of eight grass plastomes - Anderson Olin D; Lazo Gerard R; Coleman-Derr Devin; Bortiri Esteban; Gu Yong Q (BMC Research Notes, 2008)
Abstract Background Wheat, barley, and rye, of tribe Triticeae in the Poaceae, are among the most important crops worldwide but they present many challenges to genomics-aided crop improvement. Brachypodium distachyon, a close relative of those cereals has recently emerged as a model for grass functional genomics. Sequencing of the nuclear and organelle genomes of Brachypodium is one of the first steps towards making this species available as a tool for researchers interested in cereals biology. Findings The chloroplast genome of Brachypodium distachyon was sequenced by a combinational approach using BAC end and shotgun sequences derived from a selected BAC containing the entire chloroplast genome. Comparative analysis indicated that the chloroplast genome is conserved in gene number and organization with respect to those of other cereals. However, several Brachypodium genes evolve at a faster rate than those in other grasses. Sequence analysis reveals that rice and wheat have a ~2.1 kb deletion in their plastid genomes and this deletion must have occurred independently in both species. Conclusion We demonstrate that BAC libraries can be used to sequence plastid, and likely other organellar, genomes. As expected, the Brachypodium chloroplast genome is very similar to those of other sequenced grasses. The phylogenetic analyses and the pattern of insertions and deletions in the chloroplast genome confirmed that Brachypodium is a close relative of the tribe Triticeae. Nevertheless, we show that some large indels can arise multiple times and may confound phylogenetic reconstruction.